Analisis Komoditas Unggulan Subsektor Pertanian di Provinsi Bengkulu - Anggi Lestari; Sugiyanto Sugiyanto; Tungga Buana Diana (Fakultas Pertanian Universitas Borobudur, 2023)
One of the indicators of regional development performance can be seen from economic growth. This indicator provides an overview of the extent to which the economic activities of a region over a certain period of time have resulted in an increase in income for the people as indicated by an increase in per capita income. Indonesia as an agricultural country allows economic development to be prioritized in the agricultural sector. Location Quotient (LQ) analysis as a comparison of the magnitude of the role of a sector in an area to the magnitude of the role of the sector nationally. Agriculture is a leading sector/base in Bengkulu Province. The results of the LQ analysis in each food crop subsector have an LQ value of > 1, namely 2.70; horticultural crops have an LQ value > 1, namely 2.29; plantation crops have an LQ value > 1, namely 1.19; livestock has an LQ value of > 1, which is 2.53; agricultural and hunting services have an LQ value of > 1, which is 3.13. shows that the growth rate of the sectors in each district is greater when compared to the growth rate of the same sector as the economy of Bengkulu Province, the sector concerned in which the production is concerned can meet the needs of the area and can even meet the needs of outside the region